Mengatasi kejenuhan siswa kelas X Religi MA Darul Hikmah dalam belajar bahasa Arab melalui kegiatan Ice Breaking - Jamhurriah, Jamhurriah (MAN 4 Kota Pekanbaru, 2023)
This classroom action research aimed to improve the learning motivation of 23 students in the Class X Religious Program at MA Darul Hikmah Pekanbaru in Arabic Language class, using ice-breaking activities. The research was conducted in two cycles: planning, implementation, observation, and reflection. Data were collected through observation, questionnaires, and documentation. The results showed that the performance of ice-breaking activities in Arabic Language class improved the students’ learning motivation. The ice-breaking actions also contributed to a more active and enjoyable learning process. In conclusion, ice-breaking activities can effectively improve student learning motivation in Arabic Language classes. Teachers should apply this strategy in their teaching practices to create a more engaging and enjoyable learning atmosphere.